Genetic diversity of loquat germplasm (Eriobotrya japonica (Thunb) Lindl) assessed by SSR markers - Soriano, J. M.; Romero, Carlos; Vilanova, S.; Llácer, Gerardo; Badenes, María L. (2017)
Genetic relationships among 40 loquat (Eriobotrya japonica (Thunb) Lindl) accessions that originated from different countries and that are part of the germplasm collection of the Instituto Valenciano de Investigaciones Agrarias (IVIA) (Valencia, Spain) were evaluated using microsatellites. Thirty primer pairs flanking microsatellites previously identified in Malus × domestica (Borkh.) were assayed. Thirteen of them amplified polymorphic products and unambiguously distinguished 34 genotypes from the 40 accessions analyzed. Six accessions showing identical marker patterns were Spanish local varieties thought to have been derived from 'Algerie' by a mutational process very common in loquat species. A total of 39 alleles were detected in the population studied, with a mean value of 2.4 alleles per locus. The expected and observed heterozygosities were 0.46 and 51% on average, respectively, leading to a negative value of the Wright's fixation index (–0.20). The values of these parameters indicate a smaller degree of genetic diversity in the set of loquat accessions analyzed than in other members of the Rosaceae family. Unweighted pair-group method (UPGMA) cluster analysis, based on Nei's genetic distance, generally grouped genotypes according to their geographic origins and pedigrees. The high number of alleles and the high expected heterozygosity detected with SSR markers developed in Malus × domestica (Borkh.) make them a suitable tool for loquat cultivar identification, confirming microsatellite marker transportability among genera in the Rosaceae family.